Using Computer and the Internet in Preparing Teachers of Arabic to Speakers of Other Languages: The Status of Arabic Language Institute at King Saud University - Alkahtani, Saad (Jordan Journal of Educational Sciences, 2013)
This research aims to introduce the uses of computers and the Internet in the preparation of teachers of Arabic as a second language through the detection of trends in trainees’ attitudes toward the syllabus of a computer assisted language course, and whether there were statistically significant differences attributable to variables (specialization , age, and schools from which students graduated). In addition, the study investigated the contribution of the course in increasing trainees’ willingness to enroll in more technology courses. The study showed consistency in views amongst participants on the importance of the course content in general. Using the T-test, it was found that there are differences between participants depending on their specialty for the benefit of Sharia and Islamic Studies, and age in favor of younger groups, and schools for the benefit of those who have graduated from Arabic universities. The study also showed that the course has contributed to the increase of trainees’ willingness to learn more about computer and its applications in language teaching.